Short-term predictive capacity of two different triage systems in patients with acute heart failure: TRICA-EAHFE study. (December 2016) - Miró, Òscar; Tost, Josep; Herrero, Pablo; Jacob, Javier; Martín-Sánchez, Francisco Javier; Gil, Víctor; Fernández-Pérez, Cristina; Escoda, Rosa; Llorens, Pere
Abstract : Objective: To evaluate whether prioritization of patients with acute heart failure (AHF) in the Andorran Triage Model/Spanish Triage System (MAT/SET) and the Manchester Triage System (MTS) also allows the identification of different profiles of outcome and prognosis and determine whether either system has a better predictive capacity of outcomes. Patients and methods: Patients with AHF included in the Spanish EAHFE registry from hospitals using the MAT/SET or MTS were selected and divided according to the triage system used. Outcome variables included hospital admission, length of stay, death during admission, 3, 7, and 30-day all-cause mortality, and emergency department (ED) reconsultation at 30 days. The results were compared according to the level of priority and the triage system used. Results: We included 3837 patients (MAT/SET=2474; MTS=1363) classified as follows: 4.0% level 1; 34.7% level 2; 55.1% level 3; and 6.3% levels 4–5. Both systems associated greater priority with higher rates of admission and mortality; the MTS associated greater priority with greater ED reconsultation and the MAT/SET found greater priority to be associated with less ED reconsultation. The discriminative capacity of the two scales for adverse outcomes was statistically significant, albeit poor, for almost all the outcome events and it was of scarce clinical relevance (Area under the curve of the receiver operating characteristic between 0.458 and 0.661). Conclusion: The prediction of the outcome of patients with AHF determined with the MAT/SET or MTS showed scarce differences between the two systems, and their discriminative capacity does not seem to be clinically relevant. Abstract : Supplemental Digital Content is available in the text.